PENGARUH KOMUNIKASI PEMASARAN TERPADU, CITRA PERUSAHAAN OPERATOR SELULER TERHADAP VOLUME PENJUALAN PADA PT. LBC KENDARI - Zainuddin, Muh. Zabir; Lianti, Hayu; M., Suyuti H. (Sultra Journal of Economic and Business, 2020)
This study aims to determine whether integrated marketing communication and corporate image partially have a significant effect on sales volume at PT. LBC Kendari. Furthermore, this study also aims to determine the effect of integrated marketing communication and corporate image simultaneously on sales volume at PT. LBC Kendari. The method used in this research is qualitative and quantitative methods. The subjects of this study were 45 samples who were customers of PT. LBC Kendari. Data were collected using questionnaires, interviews and direct observation. Data collected is processed using the SPSS Ver . 20application.This study uses multiple linear regression analysis, partial test (t test) and simultaneous test (F test). The results showed that integrated marketing communication (X1) affected the sales volume, this was obtained based on t count> t table that is 5.391>2.01808with a significance value (0,000 <0.05). Company image (X2) has a significant effect on sales volume, this is obtained based on t arithmetic> t table that is 3.254>2.01808with a significance value (0.002<0.05). Based on the results of the study, simultaneously integrated marketing communication and company image have a significant effect on sales volume.